THE PLACE AND ROLE OF CENTRAL ASIAN THINKERS IN THE FORMATION OF UZBEK PHILOSOPHY (Scientific journal of the Fergana State University, 2024)
This article analyzes the formation of Uzbek philosophy, its essence and historical roots. It will also be explained that the works of great thinkers and scientists, including Abu Nasr Farobi, Abu Ali Ibn Sina, Abu Rayhan Beruni, Alisher Navoi, Abdullah Avloni, who laid the foundations for the formation of Uzbek philosophy, received worthy place. in the golden treasure of world civilization. At the same time, the contribution of outstanding philosophers of the twentieth century Vahid Zohidov and Ibrahim Mominov to the development of Uzbek philosophy is described.